Believing in birth - choosing VBAC: the childbirth expectations of self-selected cohort of Australian women. - Fenwick, Jennifer; Gamble, J.; Hauck, Yvonne (Blackwell Publishing, 2007)
Aim. This study explored the childbirth expectations and knowledge of women who had experienced a caesarean and would prefer a vaginal birth in a subsequent pregnancy.Background. Vaginal birth after caesarean is considered best practice. However, in most western world countries, despite the inherent risks of caesarean for both mother and baby, the number of women labouring after a previous caesarean is declining.Methods. Newspaper advertisements were used to recruit Western Australian women who had experienced a caesarean. Thematic analysis was used to analyse the interview data collected from women who attempted a vaginal birth (n = 24), or stated they would choose this option, in a subsequent pregnancy (n = 11).Findings. For this cohort of women, their caesarean experience reinforced their previously held expectations about birthing naturally. The women held strong views about the importance of working with their bodies to achieve a vaginal birth, which was considered an integral part of being a woman and mother. Positive support from family and friends and a reluctance to undergo another caesarean was also influential. Women articulated the risks of caesarean and considered vaginal birth enhanced the health and well-being of the mother and baby, promoted maternal infant connection and the eased transition to motherhood.Conclusion. This study documents how the importance of birth, as a significant life event, remained the focus of these women's childbirth expectations influencing future decisions on birth mode and mediating against the 'pressure' of medical discourse promoting caesarean.Relevance to clinical practice. Knowledge and appreciation of the multiple dimensions that contribute to women's decision after a caesarean provides valuable information on which service providers and researchers can draw as they investigate interventions that enhance the uptake and success of women birthing vaginally after a caserean.